Use of a non-navigational, non-verbal landmark task in children. (November 2013) - Overman, William; Pierce, Allison; Watterson, Lucas; Coleman, Jennifer K.
Two hundred and twenty two children (104 females), 1–8 years of age and young adults, were tested for up to 25 days on five versions of a non-verbal, non-navigational landmark task that had previously been used for monkeys. In monkeys, performance on this task is severely impaired following damage to the parietal cortex. For the basic task, the positive of two identical stimuli concealed a food reward and was designated by spatial proximity of a salient landmark. None of the 1- and 2-year-old children learned the task, i.e., they failed to consistently reach for and displace the positive stimulus in 25 test days. Of the 3-, 4-, and 5- year-old groups, 56%, 70%, and 77% of the children, respectively, mastered the task within 25 days. Children older than 5 and adults rapidly mastered the task. In Experiment #2, all subjects, 1–6 years of age, rapidly mastered a non-relational task when the choice stimulus was attached to the landmark, but the youngest children failed to transfer performance when the landmark was subsequently detached. Children under the age of 5 did not tolerate relational ambiguity as well as adults did. Replications of the first two experiments produced virtually identical results and indicated that the tests have a high degree of reliability. In Experiment #5, there were two distinct proximal landmarks, one of which always designated the positive stimulus. This manipulation did not improve performance of younger children. As compared to results from navigational landmark tasks, results obtained in the Wisconsin General Testing Apparatus (WGTA) indicate a very narrow focus of attention on the response site. Thus, small separations between discriminative cue and response site significantly affect performance, especially in younger children. By comparing the present results with those from monkeys, we speculate that components of the parietal pathways involved with attention and reaching mature between 1 and 5 years of age in children.